Issues of Women Empowerment in Anita Desai’s Novel Clear Light of Day: Exploring Women's Struggle for Empowerment in Anita Desai's Clear Light of Day (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper seeks to outline the compact of women empowerment Anita Desai’s Novel especially in her stunning novel clear light of day. In her novel Clear light of Day, Anita Desai Portrays Indian women as marginalized characters facing challenges and burdens imposed by partriarchal society. They resemble colonial subjects whose lives are fractured. Among the female characters bin, Tara, their mother and Aunt Mira, all are subordinated by male dominant culture which underestimates female subjectivity. This paper illustrates how these women manage their precarious situation and stand up to a society controlled by men. This study reflects on these women’s lives to see how they find different ways to assert their existence. One way in which these female characters survive is by entering male dominated society and adopting their language and culture. As these women are unable to improve their circumstances, they struggle to establish their own identity using the oppressor’s language and culture.